2015
DOI: 10.17269/cjph.106.5057
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge change associated with participation in prenatal education programs in Ontario: A cohort study

Abstract: This study is the first large-scale effort to examine the ability of prenatal programs offered through Ontario public health units to influence clients' pregnancy-related knowledge. These findings contribute to the evidence base for prenatal education program planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Defining clear parameters for the best timing for a parent to begin and end a PPN parenting program proved futile and is not as unexpected as the literature is inconclusive also. Whilst trimester one seems to be critical for healthy development of the preborn thus making it an effective time for parents to begin a program (Australian Institute of Health and Welfare, 2014; Godin et al, 2015); the motivation to learn about topics such as labor, birth, and breastfeeding may not be perceived as a priority so early into the pregnancy (Godin et al, 2015). Perhaps offering flexible timing for program delivery is needed until an evidence base of clinical studies that compare program effectiveness depending on start and end times are conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining clear parameters for the best timing for a parent to begin and end a PPN parenting program proved futile and is not as unexpected as the literature is inconclusive also. Whilst trimester one seems to be critical for healthy development of the preborn thus making it an effective time for parents to begin a program (Australian Institute of Health and Welfare, 2014; Godin et al, 2015); the motivation to learn about topics such as labor, birth, and breastfeeding may not be perceived as a priority so early into the pregnancy (Godin et al, 2015). Perhaps offering flexible timing for program delivery is needed until an evidence base of clinical studies that compare program effectiveness depending on start and end times are conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include a lack of control groups when PPN parenting programs are trialed (e.g., Hussaini, Holley, & Ritenour, 2011;Plantin, Olukoya, & Ny, 2011); use of small sample sizes (e.g., Goodman et al, 2014) which reduces generalizability, reliability, and validity of research outcomes; and lack of longitudinal follow up of sustainability of results measured (e.g., Peckham, 2013;Zucchi et al, 2013). Further, there is inconsistency within the literature on what constitutes most effective content (e.g., Dunneram & Jeewon, 2015;Feinberg, Roettger, Jones, Paul, & Kan, 2015), as well as best-practice for program design and delivery factors such as timing throughout a pregnancy to begin and end a program (e.g., Godin et al, 2015;Trillingsgaard et al, 2012); consumer groups (e.g., Davis, Vyankandondera, Luchters, Simon, & Holmes, 2016;Hollins Martin, & Robb, 2013;Robling et al, 2016); ways to include fathers (e.g., Deslauriers, Devault, Groulx, & Sevigny, 2012;Humphries & Nolan, 2015); length of individual sessions and programs overall (e.g., Feinberg et al, 2015); methods of delivery (e.g., Arcus, 1995;Gazmararian et al, 2014); location for program delivery (Brixval et al, 2016); and who is best qualified to facilitate (e.g., Feinberg et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Primary and secondary outcomes related to perinatal health and perinatal health determinants were identified from a literature review on group prenatal education effects [ 18 , 39 ]. Based on studies that demonstrated significant effects of group prenatal education, the main outcome for health determinant is perinatal knowledge [ 13 , 40 ] and will be measured with an adapted version of the Health Pregnancies Knowledge Survey [ 41 ]. The questionnaire will be adapted in collaboration with prenatal education trainers from the different participant training sites, in order to ensure that all knowledge items are covered in group and online prenatal education.…”
Section: Methodsmentioning
confidence: 99%
“…remainder recruited via self-referral (n ¼ 3), 27,52,57 telephone, mailed, or online surveys (n ¼ 3), 30,48,49 public health units (n ¼ 1), 43 or a random sampling of houses in a community (n ¼ 1). 29 Two studies did not state their recruitment approaches.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%